REORIENTASI PENINGKATAN KOMPETENSI SDM APARATUR DALAM PEMBERIAN LAYANAN PUBLIK - Yustiono1, Eris (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2006)
It is widely known that the country?s quality of public service is stil substandard.Theprocedures are full of twists and turns. The delivery is, most of the time, sluggish and an atmosphere of corruption seems to flourish within public service institutions. All these problems, without any doubt, reflect insufficient competence among public service apparatus. Actually, efforts to improve apparatus competence through trainings have many a time been conducted, however, the impacts have yet to be evident. This might be due to the fact that most of trainings have been conducted without feasible planning. In addition, commitment for apparatus competence upgrading from senior government officers seems to be lacking. Therefore, an alternative course of action is to be established to develop apparatus competence through proper trainings highly endorsed by a strong leadership.